Complex mechanical behavior of human articular cartilage and hydrogels for cartilage repair. (December 2020) - Weizel, A.; Distler, T.; Schneidereit, D.; Friedrich, O.; Bräuer, L.; Paulsen, F.; Detsch, R.; Boccaccini, A.R.; Budday, S.; Seitz, H.
Abstract: The mechanical behavior of cartilage tissue plays a crucial role in physiological mechanotransduction processes of chondrocytes and pathological changes like osteoarthritis. Therefore, intensive research activities focus on the identification of implant substitute materials that mechanically mimic the cartilage extracellular matrix. This, however, requires a thorough understanding of the complex mechanical behavior of both native cartilage and potential substitute materials to treat cartilage lesions. Here, we perform complex multi-modal mechanical analyses of human articular cartilage and two surrogate materials, commercially available ChondroFillerliquid, and oxidized alginate-gelatin (ADA-GEL) hydrogels. We show that all materials exhibit nonlinearity and compression-tension asymmetry. However, while hyaline cartilage yields higher stresses in tension than in compression, ChondroFiller liquid and ADA-GEL exhibit the opposite trend. These characteristics can be attributed to the materials' underlying microstructure: Both cartilage and ChondroFiller liquid contain fibrillar components, but the latter constitutes a bi-phasic structure, where the 60% nonfibrillar hydrogel proportion dominates the mechanical response. Of all materials, ChondroFiller liquid shows the most pronounced viscous effects. The present study provides important insights into the microstructure-property relationship of cartilage substitute materials, with vital implications for mechanically-driven material design in cartilage engineering. In addition, we provide a data set to create mechanical simulation models in the future. Graphical abstracts: Image, graphical abstract